2003
DOI: 10.1080/08941930390153069
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Small-Intestine Mucosal Barrier After Intestinal Occlusion: A Study with Light and Electron Microscopy

Abstract: It is known that the gut may serve as a reservoir for various microorganisms, which under specific circumstances may intrude into the systemic circulation, causing systemic infections. The aim of the present study was to estimate the "critical time" of disruption of the small-intestine mucosal barrier in conditions of experimentally induced intestinal occlusion, based on the histopathological alterations observed under light and electron microscopy. Forty rabbits underwent small-intestine obstruction through l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The histological damage in our IO rats was similar to other models of mechanical obstruction showing swollen and edematous villous structure [8,24]. The continuity of epithelial layer on the villi was not disrupted in IO rats, in comparison to models with mesenteric ischemia/reperfusion injury that display severe villous denudation and tissue necrosis [9,23].…”
Section: Discussionsupporting
confidence: 76%
“…The histological damage in our IO rats was similar to other models of mechanical obstruction showing swollen and edematous villous structure [8,24]. The continuity of epithelial layer on the villi was not disrupted in IO rats, in comparison to models with mesenteric ischemia/reperfusion injury that display severe villous denudation and tissue necrosis [9,23].…”
Section: Discussionsupporting
confidence: 76%
“…Increased bacterial loads and breakdown of tight junctions associated with intestinal obstruction are thought to promote bacterial translocation. First proposed by Deitch et al , 47, 58 intestinal obstruction has been shown to promote bacterial overgrowth, 58 and disruption of the intestinal epithelium in animal models, 48, 59, 60 resulting in an increased prevalence of bacterial translocation on univariate analysis 61 . These observations have also been substantiated by some human studies 23, 24, 46 …”
Section: Factors That Predispose To Translocationmentioning
confidence: 88%
“…Factors that influence bacterial translocation are believed to act on the delicate homeostatic equilibrium between luminal organisms and the gut barrier, promoting ingress of antigens across the intestinal barrier 44, 45 . These factors are thought to include intestinal obstruction, 23, 24, 46–48 jaundice, 23, 24, 49–52 inflammatory bowel disease, 24, 53, 54 malignancy, 55–57 pre‐operative total perenteral nutrition (TPN), 23 emergency surgery, 23 and gastric colonization with microrganisms 23, 40 . Much of the evidence to substantiate these claims is available from animal studies.…”
Section: Factors That Predispose To Translocationmentioning
confidence: 99%
“…The composition of normal intestinal microbiota is affected by various factors: diet, gastric and intestinal secretions, bile salts, lysozyme, secretory IgA, antibacterial drugs, endotoxic shock, parenteral nutrition, bowel obstruction, and much more [34]. All these factors can lead to microbiota imbalance and bacterial overgrowth, which in its turn, contributes to BT, as it is been proven in animal models [35] and in humans [36].…”
Section: Imbalance Of Normal Intestinal Microbiota and Bacterial Overgrowthmentioning
confidence: 99%